Differential Immunodominance Hierarchy of CD8T-Cell Responses in HLA-B*27:05- and -B*27:02-Mediated Control of HIV-1 Infection. - Adland, Emily; Hill, Matilda; Lavandier, Nora; Csala, Anna; Edwards, Anne; Chen, Fabian; Radkowski, Marek; Kowalska, Justyna D; Paraskevis, Dimitrios; Hatzakis, Angelos; Valenzuela-Ponce, Humberto; Pfafferott, Katja; et al. (J Virol, 2018)
The well-characterized association between HLA-B*27:05 and protection against HIV disease progression has been linked to immunodominant HLA-B*27:05-restricted CD8T-cell responses toward the conserved Gag KK10 (residues 263 to 272) and polymerase (Pol) KY9 (residues 901 to 909) epitopes. We studied the impact of the 3 amino acid differences between HLA-B*27:05 and the closely related HLA-B*27:02 on the HIV-specific CD8T-cell response hierarchy and on immune control of HIV. Genetic epidemiological data indicate that both HLA-B*27:02 and HLA-B*27:05 are associated with slower disease progression and lower viral loads. The effect of HLA-B*27:02 appeared to be consistently stronger than that of HLA-B*27:05. In contrast to HLA-B*27:05, the immunodominant HIV-specific HLA-B*27:02-restricted CD8T-cell response is to a Nef epitope (residues 142 to 150 [VW9]), with Pol KY9 subdominant and Gag KK10 further subdominant. This selection was driven by structural differences in the F pocket, mediated by a polymorphism between these two HLA alleles at position 81. Analysis of autologous virus sequences showed that in HLA-B*27:02-positive subjects, all three of these CD8T-cell responses impose selection pressure on the virus, whereas in HLA-B*27:05-positive subjects, there is no Nef VW9-mediated selection pressure. These studies demonstrate that HLA-B*27:02 mediates protection against HIV disease progression that is at least as strong as or stronger than that mediated by HLA-B*27:05. In combination with the protective Gag KK10 and Pol KY9 CD8T-cell responses that dominate HIV-specific CD8T-cell activity in HLA-B*27:05-positive subjects, a Nef VW9-specific response is additionally present and immunodominant in HLA-B*27:02-positive subjects, mediated through a polymorphism at residue 81 in the F pocket, that contributes to selection pressure against HIV.CD8T cells play a central role in successful control of HIV infection and have the potential also to mediate the eradication of viral reservoirs of infection. The principal means by which protective HLA class I molecules, such as HLA-B*27:05 and HLA-B*57:01, slow HIV disease progression is believed to be via the particular HIV-specific CD8T cell responses restricted by those alleles. We focus here on HLA-B*27:05, one of the best-characterized protective HLA molecules, and the closely related HLA-B*27:02, which differs by only 3 amino acids and which has not been well studied in relation to control of HIV infection. We show that HLA-B*27:02 is also protective against HIV disease progression, but the CD8T-cell immunodominance hierarchy of HLA-B*27:02 differs strikingly from that of HLA-B*27:05. These findings indicate that the immunodominant HLA-B*27:02-restricted Nef response adds to protection mediated by the Gag and Pol specificities that dominate anti-HIV CD8T-cell activity in HLA-B*27:05-positive subjects.